Optimise Energy Cost for Air Conditioning based on the Market Price under Demand Side Response Model - Marwan Marwan; Syafaruddin Syafaruddin (International Journal of Electrical and Computer Engineering (IJECE), 2017)
The increasing contribution of air conditioning (AC) to energy consumption has received considerable attention in the past and will continue to do so in the coming years, from Indonesian government, state electricity company and consumers. Managing demand on the electricity system in peak sessions is the most direct way to address the AC peak demand issue. The aim of this research is to developed a consumer demand side response (DSR) model to assist both electricity consumers/aggregator and electricity provider to minimise energy cost if peak price occured in the peak season. The proposed model allows consumers to independently and proactively manage air conditioning load through an aggregator. This research examines how the control system applies DSR model if a price spike may occur at 18.00 during one hour. The results indicate, consumer and aggregator could gain collective benefits when the consumer controls the air conditioning under the DSR program. The model was tested in Makassar City South Sulawesi considering to the caharacteristic of the room and air conditioning in a residential house.